One magic Christmas [videorecording (DVD)] - Steenburgen, Mary; Basaraba, Gary; Meyrink, Michelle; Hill, Arthur, 1922-2006; Stanton, Harry Dean, 1926-2017 (Disney DVD., 2004)
A young mother rediscovers the joy and beauty of Christmas, thanks to the unshakable faith of her six-year-old daughter, Abbie, and Gideon, the mother's very own guardian angel.